2006
DOI: 10.1177/1359104506067875
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Focused Short-term Preventive Counselling Project for Families with a Parent with Cancer

Abstract: Twenty-four families participated in counselling for families with a parent with cancer (24 mothers, 17 fathers, and 34 children). Parents who received counselling were significantly more depressed before the counselling than a nonrandomized control group who did not receive counselling, but participated in another part of the project. For the parents, there was a significant decrease in depression and increase in family functioning scores from before to after the intervention. For the children, a significant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
104
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(109 citation statements)
references
References 9 publications
4
104
0
1
Order By: Relevance
“…Parents and children can both be reluctant to talk about the diagnosis of cancer, trying to protect each other or just outright avoiding unpleasant discussions. It is crucial to offer opportunities of open communication for these families, including group counseling and family therapy, but should also be expanded to include peer support groups and group intervention for children involved (9,13,31).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents and children can both be reluctant to talk about the diagnosis of cancer, trying to protect each other or just outright avoiding unpleasant discussions. It is crucial to offer opportunities of open communication for these families, including group counseling and family therapy, but should also be expanded to include peer support groups and group intervention for children involved (9,13,31).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to provide support to parents in how to explain their diagnosis in an age-appropriate manner and allowing children the opportunity to express their questions and concerns, as doing so results with better coping mechanisms and decreased distress (13). The introduction of coping strategies that include distraction, wishful thinking, spending time with parents, helping parents, and peer support also help decrease stress and distress (13,27,31). For adolescents, providing avenues for them to connect to other peers in similar situations is important as adolescents report better support from friends whose parents also have cancer, as they find it difficult to relate or express ideas to their unaffected friends (15).…”
Section: Interventionsmentioning
confidence: 99%
“…Above all, counsellors, and in particular counsellors/social workers working in hospital settings, need to be aware that support and/or interventions must include all members of the family, not only the spousal caregiver, as typically has been the current focus of counselling practices (Thastum, Munch-Hansen, Wiell, & Romer, 2006). Despite the need for emotional support, the accounts of these adult children showed that, for the most part, their journey was one of isolation.…”
Section: Implications For Counsellingmentioning
confidence: 99%
“…Although the findings also showed that the variability in study populations and intervention design makes generalising findings from studies difficult (ibid. ), family interventions in oncological care addressing the whole family have shown improvements in quality of life, psychological health and depressive symptoms in parents as well as children (John et al, 2013;Thastum et al, 2006).…”
Section: The Families' Need For Supportmentioning
confidence: 99%
“…Although the findings also showed that the variability in study populations and intervention design makes generalising findings from studies difficult (ibid. ), family interventions in oncological care addressing the whole family have shown improvements in quality of life, psychological health and depressive symptoms in parents as well as children (John et al, 2013;Thastum et al, 2006).Family Health Conversations (FamHC) were developed in Sweden by Benzein and colleagues (2008; by culturally adapting the practice models of Family Systems Nursing , 2013. Family-focused care is grounded in the belief that health and illness in a family member affect the other family members both as individuals and as a family , and it has a systemic approach that focuses on the interactions and relationships within the family with the aim of preserving health and facilitate healing.…”
mentioning
confidence: 99%